Respostas

2014-04-15T17:55:05-03:00
1) x² -4x -5 =0  
x= -(-4) +- √ -4² -4.1.-5  
               2 
x = 4 +- √16 +20  
            2 
x = 4+- √36  =
           2
 x = 4 +- 6 
          2
x¹ = 4+6 = 10  =  5
         2       2
x² = 4-6  = -2 = -1 
        2        2 
                             D) {5 - 1} 
 
 
Sei a 1 . 

1 5 1
A melhor resposta!
2014-04-15T17:57:02-03:00
(a) (b) (c)
x² -4x -5=0         Δ=b²-4.a.c
                         Δ=(-4²)-4.1.(-5)
                         Δ=16+20
                         Δ= 36

-b +ou- √Δ ÷ 2.a

-(-4)+ ou - 6 ÷ 2              -(-4) + ou - 6 ÷2
-2 ÷ 2 = -1                        10 ÷ 2
x' =  -1                          x''=5
              S {-1 ; 5}


hipotenusa é igual
a²+b² = h²

5²+12² = h²
-h²= -169 .(-1)
 h = √169
 {h = 13}


1 5 1